Stable C and N isotope abundances in water-extractable organic matter from air-dried soils as potential indices of microbially utilized organic matter - Nagano, Hirohiko; Atarashi-Andoh, Mariko; Tanaka, Sota; Yomogida, Takumi; Kozai, Naofumi; Koarashi, Jun (Frontiers in Forests and Global Change, 2023)
Stable carbon (C) and nitrogen (N) isotopes (13C and 15N) in water-extractable organic matter (WEOM) derived from air-dried soils may be applicable to elucidate the microbial decomposition of soil organic matter (SOM), which is crucial in terrestrial C cycles. A total of 40 soil samples were collected from a depth of 0–6 cm from a temperate broadleaved forest in Japan with vegetation succession from grassland approximately 150 years ago. Those soil samples were air-dried before the water extraction process and organic matter analysis. The C and N concentrations of WEOM were <3.6% of those of the bulk soil and were positively correlated with those of the bulk soil at a p-value of < 0.01. A positive correlation between the two fractions (i.e., WEOM and bulk soils) was also found for natural 13C and 15N abundances (δ13C and δ15N; p < 0.01). However, the C/N ratio of WEOM was slightly correlated with that of bulk soils, exhibiting a narrow range of values of 10. Thus, those features of the WEOM were similar to the well-known features of microbial biomass. The δ13C and δ15N enrichments in WEOM relative to bulk soil, the difference in stable isotope abundances between bulk SOM and WEOM were negatively and positively correlated, respectively, with the concentrations of organo-mineral complexes and short-range order minerals (non-crystalline oxyhydroxides of aluminum and iron, allophane, imogolite, and allophane-like constituents), which play significant roles in SOM stabilization in soils. These relationships suggest that the stable isotopic enrichments in WEOM can be a good indicator of the microbial utilization of soil C and N under different substrate availabilities, which are crucial to SOM decomposition and decomposability substantially varying from local to global scales.